Lexicographic Analysis of Linguistic Terms in Annotated Proverbs in English and Uzbek Languages - Mirzaahmedov Mirjalol Mansurjon ugli (Periodica Journal, 2023)
The given thesis reveals the essence about the language, as the most important element of speech, plays a major social role in transmitting the experience and knowledge accumulated in human society to future generations. Language as a form of culture perpetuates the fruits of thought and cultural values that constantly anticipate each other in time and space and contribute to mutual existence and development. Thinking is unique to man. It exists in conjunction with people’s labor and speech activities. Thinking is manifested through speech and is coded in language as a result. Language is a mirror of people's hearts. The language reflects the nation's art, literature, history, traditions, worldview, aspirations, and patriotic feelings. Every word and every form of it is the result of thinking and feeling. The peculiarities of the homeland and the people are expressed through language. Respect for the mother tongue and the proper use of its invaluable potential, clear and effective speaking and writing, and the achievement of speech literacy are the primary duties of everyone who is a mother tongue in that language
Keywords: mentality; traditions; worldview; thinking